Increased Production of Mustard (Brassica juncea L.) with Application Capillary-Irrigation System - Amprin Amprin; Joko Suryanto (Universitas 17 Agustus 1945 Samarinda, 2019)
Increased Production of Mustard (Brassica juncea L.) with Application Capillary-Irrigation System. Application of capillary irrigation system on mustard is expected to increase the crop productivity. The aims of this study was to calculate the use of water of mustard with application capillary irrigation using wick and flanneland to determine the best combination of irrigation capillary tools of capillarity system. The design of this study used two factors and three replications. The first factor was wick materials (S), consistings two level: the flannel wick (S1), and stove wick (S2). The second factor was the dosage sawdust (M), consists two level: 0 % of sawdust (M1), and 50 % of sawdust (M2).The research results showed that total water use of M1S1 is 169.7 ml and M1S2 is 107,91 ml, M2S1 is 198.4 ml, and M2S2 is 151.76 ml. The best combination of this research obtain on M2S1, the second cultivating media, the soil by using soil with silty clay loamtexture which mixed50 % of sawdust and the wick of flannel.